(3GdhLjR aj CSeGA GdQLGds - (3eMeO HGbQ Hf eMeO Jbj Hf ebUhO Ydj GdCUagGfj, J (B1111 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi QaY efGRd GdQLGd s
(3Vef eLehY , JQJjHgG (B: (3ef U (B1 - (3U(B30s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B48 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B91s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B2 - (3U (B175 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3eUWdM GdfMd GdESdGejI (B18) s
Keywords: (3GdJGQjNs